2-D microflow generation on superhydrophilic nanoporous substrates using epoxy spots for pool boiling enhancement. (April 2020) - Najafpour, S.; Moosavi, A.; Rad, S.V.
Abstract: We conduct an experimental investigation on the pool boiling enhancement in DI water on nanoporous surfaces. The surfaces are modified by anodic oxidation, and cavities with 2 mm diameter and pitches between 2.5 and 5 mm applied on them using EDM method filled with a two-part epoxy with low thermal conductivity properties. The capillary wicking action of the superhydrophilic nanoporous oxide layer enhances the rewetting and spreading of the liquid to dry-spots during boiling. The epoxy disks remain wet and prevent merging bubbles during the pool boiling experiment and a 2-D microflow is induced toward dried regions with synergic effects of nanoporous surface absorption, create a considerable delay in the formation of a vapor blanket. The results indicate that the anodized surface enhances the critical heat flux (CHF) by 33% and the heat transfer coefficient increases by 48% at the CHF compared to the non-coated substrate. It has been shown that for anodized samples with 3 and 4 mm epoxy spot pitches the CHF equals to 144 and 133 W/cm 2, respectively, considerably higher than the coated surface without epoxy parts 125 W/cm 2 .